2023
DOI: 10.1158/2767-9764.crc-22-0389
|View full text |Cite
|
Sign up to set email alerts
|

African American Prostate Cancer Displays Quantitatively Distinct Vitamin D Receptor Cistrome-transcriptome Relationships Regulated by BAZ1A

Abstract: African American (AA) prostate cancer associates with vitamin D3 deficiency, but vitamin D receptor (VDR) genomic actions have not been investigated in this context. We undertook VDR proteogenomic analyses in European American (EA) and AA prostate cell lines and four clinical cohorts. Rapid immunoprecipitation mass spectrometry of endogenous protein (RIME) analyses revealed that nonmalignant AA RC43N prostate cells displayed the greatest dynamic protein content in the VDR complex. Likewise, in AA cells, Assay … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…Beyond direct epigenetic regulation within promoter regions, gene expression changes were also contributed by reprogrammed enhancers looped to these promoters. Consistent with the conclusion that OC2 has the capability to bind to closed chromatin and promote chromatin accessibility, we show that OC2 interacts with SMARCA4 and SMARCA5, which are important components of CRCs that modify chromatin architecture to allow TF access to condensed chromatin [45,46]. Inactivation of CHD1, another chromatin remodeler, has been shown to promote the emergence of tumor heterogeneity and enzalutamide resistance [47].…”
Section: Discussionsupporting
confidence: 88%
“…Beyond direct epigenetic regulation within promoter regions, gene expression changes were also contributed by reprogrammed enhancers looped to these promoters. Consistent with the conclusion that OC2 has the capability to bind to closed chromatin and promote chromatin accessibility, we show that OC2 interacts with SMARCA4 and SMARCA5, which are important components of CRCs that modify chromatin architecture to allow TF access to condensed chromatin [45,46]. Inactivation of CHD1, another chromatin remodeler, has been shown to promote the emergence of tumor heterogeneity and enzalutamide resistance [47].…”
Section: Discussionsupporting
confidence: 88%
“…To examine how components of the RARγ complex impacted AR gene regulation we used partial correlation analyses to test the impact of coregulators in the RARγ complex on the relationship between AR expression and genes associated with AR bound in active enhancers by using the SU2C cohort of advanced PCa ( Figure 8B ). This demonstrated that several of the coregulators in the RARγ complex, including SSRPI(98) and BAZ1A(95), significantly and positively impacted the strength of the correlations between AR expression and AR enhancer dependent target genes.…”
Section: Resultsmentioning
confidence: 95%
“…Secondly, we tested if RARγ-dependent augmentation of ChromHMM-categorized AR cistrome significantly impacted the dependent-transcriptome relationships(21) by applying a modified BETA method as previously(83,95). We constructed a weighted cistrome-transcriptome score per peak binding site per gene per cell background (wt-C-T), and tested whether these values were significantly changed between ChromHMM states, treatments and cell backgrounds; all relationships are shown in Supplementary Figure 16B .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations